Reliability Assessment of Safety-Critical Systems of Nuclear Power Plant using Ordinary Differential Equations and Reachability Graph - Kumar Jyotish N.; Kumar Singh L.; Kumar C. (My University, 2025)
This study proposes a novel and integrated approach incorporating reachability graph (RG) and ordinary differential equations (ODE) to assess the reliability of safety–critical systems (SCS). The suggested framework is divided into nine steps. The system is first modeled using the Petri net (PN) to generate the ODE and RG. The ODE solution can be used to compute the marking probabilities of PN model. The marking probability values can be utilized to measure the state probabilities of RG. The resulting RG contains various states of the system. The failure states of RG are identified to assess the system's reliability. The suggested approach is implemented on the Shutdown System of Nuclear Power Plant, and is validated using Brown & Lipow model. The obtained accuracy of 99.53905% in the evaluation of reliability validates the technique. The state-space explosion is one of the major problems associated with conventional stochastic approaches like Markov chains, which use assumed transition probabilities to quantify reliability between different states. The proposed strategy is capable of avoiding the problem of state-space explosion. © 2023 Elsevier B.V.